Development and validation of a novel staging system integrating the number and location of lymph nodes for gastric adenocarcinoma - Li, Ziyu (Br J Cancer, 2020)
BACKGROUND: Evidence suggests that the anatomic extent of metastatic lymph nodes (MLNs) affects prognosis, as proposed by alternative staging systems. The aim of this study was to establish a new staging system based on the number of perigastric (PMLN) and extra-perigastric (EMLN) MLNs. METHODS: Data from a Chinese cohort of 1090 patients who had undergone curative gastrectomy with D2 or D2 plus lymphadenectomy for gastric cancer were retrospectively analysed. A Japanese validation cohort (n = 826) was included. Based on the Cox proportional hazards model, the regression coefficients of PMLN and EMLN were used to calculate modified MLN (MMLN). Prognostic performance of the staging systems was evaluated. RESULTS: PMLN and EMLN were independent prognostic factors in multivariate analysis (coefficients: 0.044, 0.115; all P < 0.001). MMLN was calculated as follows: MMLN = PMLN + 2.6 × EMLN. The MMLN staging system showed superior prognostic performance (C-index: 0.751 in the Chinese cohort; 0.748 in the Japanese cohort) compared with the five published LN staging systems when MMLN numbers were grouped as follows: MMLN0 (0), MMLN1 (1–4), MMLN2 (5–8), MMLN3 (9–20), and MMLN4 (>20). DISCUSSION: The MMLN staging system is suitable for assessing overall survival among patients undergoing curative gastrectomy with D2 or D2 plus lymphadenectomy.